The effect of coronavirus on the body’s immune system (the literature review) - Berukkyzy, A.; Ablaihanova, N.T.; Tusupbekova, G.A.; Kozhamzharova, L.S. (Fundamental and Experimental Biology, 2022)
This article presents the scientific review on the functional state of the living organism in coronavirus disease (COVID-19). Increased cytokine release in response to viral infection, known as cytokine release syndrome or cytokine storm, becomes a mechanism leading to acute respiratory distress syndrome (ARDS) and multiple organ failure (MOF) in COVID-19, thus supporting the hypothesis that appropriately selected anti-inflammatory therapeutic strategies can improve clinical outcomes and patient progress. Cytokines are low molecular weight proteins secreted by the body’s immune cells, in normal amounts have a protective effect on the body related to the delimitation of damaged tissue during inflammation. Currently, there are more than 30 types, divided into several independent groups according to their structural features and biological action. As there are no uniform diagnostic criteria for a cytokine storm, the main focus of laboratory diagnosis is on elevations of interleukin-1β (IL-1β), interleukin-6 (IL-6), C-reactive protein (CRP) and ferritin, procalcitonin.